Improving reproductive health care services for women with a physical disability: Insights from a community survey of women with spinal cord injury in Switzerland. Issue 6 (2020) - Bertschy, Sue; Ehrmann, Cristina; Stute, Petra; Skempes, Dimitrios; Maurer-Marti, Franziska; Gemperli, Armin
No abstract available